Pocket Filipino dictionary - Perdon, Renato (Periplus dictionaries, 2002)
The Philippines Pocket Tagalog Dictionary is an essential tool for communication and a great way to learn Tagalog. It features all the essential Tagalog vocabulary appropriate for beginning to intermediate students. It's handy pocket format and easy-to read type will make any future trip to The Philippines much easier